Hipóteses de cabimento de agravo de instrumento: a teoria da taxatividade mitigada adotada pelo Superior Tribunal de Justiça e os limites de interpretação da lei no Estado Democrático de Direito - Kehl, Gustavo Rafael (Universidade do Vale do Rio dos Sinos, 2020)
The 2015 Civil Procedure Code expressly provided for the possibility of an interlocutory appeal. The present work intends to verify the perspective of the legislator when establishing a list foreseeing these hypotheses, the possible problems resulting from this, the doctrinal positions regarding its interpretation and, above all, the jurisprudence of the Superior Tribunal de Justiça in this regard, especially the resources selected as representative controversy of Theme nº 988, in which the thesis of mitigated taxation remained fixed, which establishes the urgency of the appeal due to the futility of the future judgment on appeal. Specifically in relation to the judgment of the repetitive appeals that originated Theme nº 988, it is intended to investigate the problems arising from the application of the thesis set forth in the trial, to see how the Superior Tribunal de Justiça analyzed the issue before and how it started to analyze it after the judgment and verify the interpretation carried out regarding the list of hypotheses for fitting the interlocutory appeal provided for in art. 1.015 of the Civil Procedure Code. Still on this judgment, we intend to analyze it from the philosophical hermeneutics, then demonstrate that it was a pragmatic decision and also examine whether the limits of the Judiciary were observed in the interpretation of the law in a Democratic State of Law or if represented a practice of judicial activism.
Keywords: Agravo de Instrumento; Taxatividade mitigada; Hermenêutica; Pragmatismo Jurídico; Ativismo Judicial; Instrument appeal; Mitigated taxativity; Hermeneutics; Legal pragmatism; Judicial Activism